Development Trends of Multicultural Education for the Sustainable Development Goals (SDGs): Bibliometric Analysis of the Scopus Database (2010-2024) - Muhammad Abdur Rozaq; Toni Ardi Rafsanjani; Lutfiyani; Deki Wibowo; Septina Rahmawati; Devy Aufia Abshor; Muhammad Maga Sule (Profetika: Jurnal Studi Islam, 2024)
Objective: This study aims to analyze the research trends in multicultural education indexed in the Scopus database (2010–2024) using a bibliometric approach. The research specifically addresses gaps in the systematic mapping of global research patterns, thematic and geographical distribution, and international collaboration in multicultural education literature. Theoretical framework: The theoretical framework of this study is grounded in critical multicultural education theory, which emphasizes inclusivity, equity, and cultural responsiveness in educational systems. By linking this framework to the Sustainable Development Goals (SDGs)—particularly SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities)—this research underscores the role of multicultural education in achieving global sustainability objectives. Literature Review: A review of existing literature highlights extensive qualitative discussions but reveals a lack of quantitative bibliometric analysis in mapping research developments in this field. Methods: This study employs bibliometric analysis to examine annual publication trends, emerging themes, patterns of international collaboration, and geographical distribution. The research identifies leading authors, influential institutions, and key journals that contribute to the advancement of multicultural education literature. Results: The findings indicate a significant increase in research publications over the past decade, with growing international collaboration among scholars. However, disparities remain in the geographical distribution of research, with certain regions being underrepresented. Additionally, key themes such as intercultural dialogue, curriculum development, and inclusive pedagogy have gained prominence, reflecting the evolving academic discourse in multicultural education. Implications: This study has practical and theoretical implications. Theoretically, it enriches the literature by providing empirical data on global research trends. Practically, it offers strategic insights for policymakers, educators, and researchers in formulating effective policies and pedagogical strategies that integrate multicultural values into education. Novelty: The novelty of this research lies in its systematic bibliometric analysis, which provides a comprehensive mapping of multicultural education scholarship about the SDGs. This study serves as a foundational reference for future research and policy development aimed at building a more just, peaceful, and inclusive global society.